Access to community-based HIV services among transgender women in Cambodia: findings from a national survey - Siyan Yi; Say Sok; Srean Chhim; Pheak Chhoun; Navy Chann; Sovannary Tuot; Phalkun Mun; Marija Pantelic (BMC, 2019)
Abstract Background Globally, the prevalence of HIV among transgender women is more than 40 times higher than the prevalence in the general reproductive-age adults. They also face intersecting barriers to health, social, and legal services due to their hidden and stigmatized nature. Despite the particular needs, data regarding the access to services among transgender populations is scant globally. This study aims to identify characteristics of transgender women in Cambodia that may determine their accessibility to community-based HIV services. Methods In the National Biological and Behavioral Survey 2016, a structured questionnaire was used for face-to-face interviews with 1375 sexually active transgender women recruited from the capital city and 12 other provinces using the Respondent-Driven Sampling method. Weighted multivariate regression analysis was conducted to explore factors associated with access to community-based HIV services. Results The mean age of the participants was 25.8 years (SD = 7.1), and 45.0% reported having received at least one community-based HIV service in the past three months. Compared to participants who reported not having been reached by any community-based HIV programs, participants who reported having been reached by the programs were significantly more likely to reside in an urban setting (AOR = 1.41, 95% CI = 1.01-1.96), to have used gender-affirming hormones (AOR = 1.50, 95% CI = 1.17-1.92), to have been tested for HIV in the past six months (AOR = 7.42, 95% CI = 5.78-9.53), and to have been arrested by police or other authorities because of their transgender identity (AOR = 1.55, 95% CI = 1.03-2.33). Participants who reported having been reached by community-based HIV programs were significantly less likely to report being in a receptive role (AOR = 0.34, 95% CI = 0.15-0.82), to use condoms consistently with non-commercial male partners (AOR = 0.72, 95% CI = 0.55-0.94), and to perceive that their co-workers were not supportive regarding their transgender identity (AOR = 0.57, 95% CI = 0.44-0.98). Conclusions Despite the extensive expansion of community-based HIV programs, less than half of transgender women in this national survey had access to the services. Innovative strategies and culturally sensitive interventions should be put in place to reach and respond to the needs of sub-groups of transgender women who are less likely to be reached by the existing traditional approaches.